Healthcare Workers' attitudes towards mandatory influenza vaccination: a systematic review. (13th November 2019) - Corezzi, M; Gualano, M R; Voglino, G; Olivero, E; Rossello, P; Bert, F; Siliquini, R
Abstract: Background: Influenza affects approximately between 5 to 10% of general population every year, leading to 3 to 5 million cases of severe illness, and about 290 000 to 650 000 respiratory deaths. Healthcare Workers (HCWs) play a crucial role in spreading the infection to patients. Although the strong recommendations provided, influenza vaccination coverage rates among HCWs are globally well below the coverage target set by WHO. The aim of this study is to assess attitudes towards mandatory influenza vaccination programs among HCWs, in order to make a quantitative synthesis of the phenomenon. Methods: The present study systematically reviewed published cross-sectional studies investigating attitudes towards compulsory influenza vaccination in Healthcare Workers. PubMed and Scopus scientific databases were searched and 4, 198 results were returned. Of these, 23 met the inclusion criteria for the review and 13 were eligible for the meta-analyses. PRISMA statements were followed. Results: Thirteen studies were conducted in North America, 4 were conducted in Europe, 3 in Asia, 2 were performed in Australia and one study collected data both from Europe and Asia. According to the assessed studies, the percentage of agreement ranged from 44% to 95% for different compulsory vaccination programs. A combined prevalence of 59.8% (95%CI 50.1-68.8) was found in the meta-analysis. Having been vaccinated against influenza in the previous year increases the likelihood (OR 4.1; 95%CI 2.8-6.1) of being in favour of mandatory vaccination policies. Conclusions: Compulsory influenza vaccination programs are generally accepted by the majority of health professionals, especially by those who have already been vaccinated previously. These results could be important to improve European vaccination strategies, in order to increase influenza vaccination rates among Healthcare Workers. Key messages: Mandatory influenza vaccination programs are accepted by the majority of Healthcare Workers. Having been previously vaccinated against influenza increases the likelihood of being in favor of a mandatory vaccination policy.